An Overview of Recent Possibilities in Pharmacotherapy of Diseases of the Oral Mucosa, Salivary Glands, and Periodontal Tissue - R. Slezák; I. Lindrová; V. Buchta; V. Paulusová; Z. Šustová; O. Kopecký; L. Ryšková (Czech Dental Chamber, 2013)
Introduction: A review of newer drugs for topical or systemic administration useful in contemporary dentistry in the therapy of diseases of periodontal tissue, oral mucous membrane, and salivary glands available in Czech Republic was given in this article. Objectives: There were discussed mouthrinses containing chlorhexidine in lower concentrations and/or oxidation agents associated with reduced dark discoloration of teeth and lingual mucosa. FotoSan 630 represents a system for photodynamic antimicrobial therapy using monochromatic light produced by light-emitting diods for the photoinitiation of the toluidine blue O as a photosensitizer. It is declared for the supportive topical treatment of plaque-induced periodontopathies, periimplant defects, dry socket, infected root canals and caries lesions. Hyaluronic acid contained in commercial gel products Aloclair and Gengigel, lubricative product Aequasyal, and gel product SineHerp are recommended in topical treatment of various less serious diseases of the oral mucosa and salivary glands. Drugs for systemic administration discussed here are antileukotriene immunomodulator montelucast, immunosuppressive and antiinflammatory drugs thalidomide and leflunomid. They are usable in the therapy of more serious mucosal diseases, mostly of autoimmune or uncertain origin. Caspofungin, micafungin and anidulafungin are modern echinocandin antimycotics for parenteral use indicated for treatment of severe mycotic infections, mostly candidiasis in altered individuals. Drugs for biological therapy declared as antitumorous and antiinflammatory agents already seldom used in dentistry are monoclonal antibodies rituximab, cetuximab, and erlotinib, potentially useful are also etanercept, infliximab and adalimumab. Botulotoxin is a neurotoxin of bacterial origin used at present in the therapy of various neurological disturbances in the head and neck area.